2005
DOI: 10.2519/jospt.2005.35.1.16
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fluidotherapy on Superficial Radial Nerve Conduction and Skin Temperature

Abstract: Study Design: Cross-sectional study. Objectives: The purpose of this study was to examine the effects of the superficial heating modality, Fluidotherapy, on skin temperature and on sensory nerve action potential (SNAP) conduction latency and amplitude of the superficial radial nerve in healthy individuals. Background: Fluidotherapy is a dry, superficial heating modality, which also provides tactile stimulation through the bombardment of air-fluidized cellulose particles. Previous literature has documented a di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Therefore, it was used in this study to provide continuous thermal stimulation. Also, the temperature was set to 48 °C because it proved to be the most effective way to transmit heat to the soft tissues by 46.7–48.9 °C at clinical application temperature 15 ) . Thermal simulation over the threshold in the peripheral nerve generates a nerve activity potential, which propagates along the motor and sensory nerves.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, it was used in this study to provide continuous thermal stimulation. Also, the temperature was set to 48 °C because it proved to be the most effective way to transmit heat to the soft tissues by 46.7–48.9 °C at clinical application temperature 15 ) . Thermal simulation over the threshold in the peripheral nerve generates a nerve activity potential, which propagates along the motor and sensory nerves.…”
Section: Discussionmentioning
confidence: 99%
“…Thermal simulation over the threshold in the peripheral nerve generates a nerve activity potential, which propagates along the motor and sensory nerves. Kelly et al reported a statistically significant change in skin temperature (p<0.001) and nerve activity potential (p<0.001) using fluidotherapy, suggesting the need for intervention in the form of surface geating to restore upper extremity function 10 ) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Percutaneous radiofrequency treatment has been reported to be a beneficial local denervation therapy for knee OA 12 ) . In the peripheral nerve fibers, the elevation of the superficial skin temperature is accompanied by an increase in the nerve conduction velocity with a concomitant decrease in sensory latency 13 ) . Although its clinical significance needs to be elucidated, nerve conduction velocity increases by approximately 2 m/s as the temperature increases by 1 °C, and this is thought to be related to nerve denervation or an increase in the pain threshold.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in the concentration of type I collagen that is seen in capsular disorders, such as adhesive capsulitis, leads to decreased range of movement (5). Increasing the temperature by 1 °C can have several effects in the human body, such as changes in nerve conduction speed, enzyme activity and oxyhaemoglobin release (6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%